IMPLEMENTASI PERLINDUNGAN HUKUM TERDAHAP HAK MATERNITAS PEKERJA WANITA DI KAWASAN BERIKAT NUSANTARA (KBN) CAKUNG JAKARTA UTARA DITINJAU DARI UNDANG-UNDANG KETENAGAKERJAAN (STUDI KASUS PELANGGARAN HAK MATERNITAS PEKERJA WANITA DI WILAYAH KBN CAKUNG, JAKARTA UTARA) - Melisa Kurniawan Ardianto; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2018)
This research was conducted to examine the rules concerning the protection of maternal right of women workers set forth in Labor Law. Basically, women workers have special right, their right must also be facilitated. One of the most fundamental right is the maternal right of women workers, including the right to menstruation leave, get social security in the form of care during childbirth and after childbirth, breast feeding and caring for the right and child rearing. This research also to look at the law as the principles of truth and justice that is natural and universally applicable. The method used in this research is normative research specifications. Juridical instruments used are equipped with the Labour Law Regulations related of legislation law, while the normative aspect associated with the materials related to the research literature. Implementation of maternity rights protection of women workers has been stated in the Labour Law and ILO Convention No. 183 Year 2000 on Maternity Protection (ILO Convention on Maternity Convention). The results of this research indicate that the implementation of maternity right not going well.